The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21303/2313-8416.2021.002036
|View full text |Cite
|
Sign up to set email alerts
|

The socio-economic impact of the Covid-19: a South African perspective on its impact on the socio-economic, inequality, security, and food systems

Abstract: The objects of this research are: first, to highlight some of the socio-economic impact, arising out of the government's strict lockdown rules due to the Covid-19 pandemic. Second, to explore the psychological effects of the new normal on citizens, arising out of the lockdown. The author investigated the following problems: social problems, caused by restricted movements, increase interpersonal violence crimes, and economic problems due to job losses, emanating from several businesses closures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Even during the partial lockdown, at supermarkets, the researcher observed that the queues for customers waiting to serve alcohol were far much longer than that of customers purchasing food. This was an eye opener for some of us who have previously underestimated the level of alcohol as part of our social existence in South Africa [17].…”
Section: Cannabismentioning
confidence: 99%
“…Even during the partial lockdown, at supermarkets, the researcher observed that the queues for customers waiting to serve alcohol were far much longer than that of customers purchasing food. This was an eye opener for some of us who have previously underestimated the level of alcohol as part of our social existence in South Africa [17].…”
Section: Cannabismentioning
confidence: 99%
“…It was reported that greater than 10 % of murderers have Autism Spectrum Disorder (ASD) and a similar majority of them have injured their heads. Moreover, these offenders have encountered psychosocial factors including parental divorce, sexual or physical abuse, and have also undergone major surgery as an adolescent [22]. The author argued that the family structure was affected by harsh working conditions under the apartheid era in South Africa.…”
Section: Culture Of Violencementioning
confidence: 99%